Konsep Kesatuan Iman, Iptek dan Amal Menuju Terbentuknya Insan Kamil dalam Perspektif Pendidikan Islam - Qurrotul Ainiyah; Karsiyah Karsiyah (ISTAWA, 2017)
In addition to the physical and spiritual goals, Islamic education also observe the purpose of reason. This aspect of purpose rests on the development of an intelligence within the brain. So, capable to understand and analyze the phenomena of God's creation in this universe. The formation of Insan Kamil in the Islamic Education Perspective is: If the reason works optimally, its intuition is functional, able to create culture, adorns it self with divinity, morality, and balanced spirit. While the concept of Faith, Science and charity are: Faith is the embodiment of Tawakkal, Introspective and be scientific, optimistic and consistent and keep the promise. Science and technology in Islam is as human needs in order to achieve prosperity of life in the world in order to provide ease in improving ubudiyah to Allah, then an act can be judged as a charity is if done with sincere selfless sincerity in humans and in accordance with the guidance of the Qur'an and Hadith. The concept of Faith, Science and Charity to the formation of Insan Kamil in Islamic Education Perspective is: Intellect functioning optimally and able to create culture is part of human character kamil which is manifestation (embodiment) of science applying values in human life, Himself with the nature of divinity and intuition that function is a manifestation of the value of human faith, noble and balanced spirit is a manifestation of human amaliyah during the world.